The relationship between favorable conditions for innovation in technology parks, the innovation produced, and companies' performance: A framework for an analysis model - Lucas Bonacina Roldan; Peter Bent Hansen; Domingo Garcia Pérez de Lema (Innovation & Management Review, 2018)
Purpose: Innovation is today considered a competitive differential for improving the performance of companies, and technology parks are seen as environments with favorable conditions for such innovation. The purpose of this study is to develop a framework for analyzing favorable conditions for innovation in technology parks, the innovations produced and organizational performance. Design/methodology/approach: To this end, the authors conducted bibliographic research and in-depth interviews with managers of companies based at the Tecnopuc Science and Technology Park, and managers of the park itself, to establish practical support for previous theoretical findings. Findings: As a result, a framework was developed to link the favorable conditions for innovation, and organizational performance. Research limitations/implications: The analysis model proposed here synthesizes the contributions made by several scholars on the theme, allowing for a more detailed and integrated interpretation of the phenomenon, namely, the ways through which the effective development of innovation takes place in companies residing in technology parks and the contribution of innovation to the specific performance of companies. Practical implications: The use of the proposed framework can help direct park managers' action towards those relationships or activities that prove to be ineffective in achieving desired goals. Originality/value: The use of the proposed model in empirical surveys will allow for better understanding of the phenomenon involving the features of technology parks and their effects on innovation and the performance of companies installed there, considering that such parks allow them to access resources with lower transaction costs.
Keywords: 650; Organizational performance; Company innovations; Favorable conditions for innovation; Technology parks